Parton splitting scales of reclustered large-radius jets in high-energy nuclear collisions - Shan-Liang Zhang; Meng-Quan Yang; Ben-Wei Zhang (European Physical Journal C: Particles and Fields, 2022)
Abstract We carry out the first theoretical investigation on yields and the hardest parton splitting of large-radius jets reclustered from small radius ( $$R=0.2$$ R = 0.2 ) anti- $$k_t$$ k t jets in Pb + Pb collisions, and confront them with the recent ATLAS measurements. The Linear Boltzmann Transport (LBT) model is employed for jet propagation and jet-induced medium excitation in the hot-dense medium. We demonstrate that, with their complex structures, the medium suppression of the reclustered large radius jets at $$R=1$$ R = 1 is larger than that of inclusive $$R=0.4$$ R = 0.4 jets defined conventionally. The large radius jet constituents are reclustered with the $$k_t$$ k t algorithm to obtain the splitting scale $$\sqrt{d_{12}}$$ d 12 , which characterizes the transverse momentum scale for the hardest splitting in the jet. The large-radius jet production as a function of the splitting scale $$\sqrt{d_{12}}$$ d 12 of the hardest parton splitting is overall suppressed in Pb + Pb relative to p + p collisions due to the reduction of jets yields. A detailed analyses show that the alterations of jet substructures in Pb + Pb also make significant contribution to the splitting scale $$\sqrt{d_{12}}$$ d 12 dependence of the nuclear modification factor $$R_{AA}$$ R AA . Numerical results for the medium modifications of the jet splitting angle $$Δ R_{12}$$ Δ R 12 and the splitting fraction z are also presented.